The Experiences of Refugee single mothers during the Covid-19 pandemic in the Ottawa Region Ontario, Canada. - Osobajo, Aderonke (Université Saint-Paul / Saint Paul University, 2023)
This paper presents some findings from refugee single mothers living in Ottawa, Canada, exploring their employment experiences and experiences as single mothers during the Covid-19 period. It also covers how to generate evidence to guide policy development, considering the access to resources and refugee single mothers' financial stability, especially during the Covid-19 pandemic. My analysis draws on six interviews with refugee single mothers. It shows that all refugee single mothers faced a difficult situation during the pandemic and post-pandemic, especially in getting employment, providing necessities for the family and caring for their children. Finally, the paper presents a theoretical and conceptual framework empirically grounded in an innovative qualitative methodological design to capture the complexities of the research, using participants’ narratives as the empirical material.
Keywords: Keywords: Covid-19, Pandemic, Refugee, Single Mother, Migrants, employment